Deregulasi Hak Upah dan Pesangon Pekerja dalam Undang-Undang Cipta Kerja Melalui Konsep Omnibus Law - Moh Hamzah Hisbulloh; Ruslina Dwi Wahyuni (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
The Job Creation Act came as a deregulation of past regulations, one of which was related to severance pay and wages, in its ratification the Job Creation Act was rejected by the public, because it was considered detrimental to both the legislative process without public participation and also the abolition of wage points and severance pay. The content material in the Job Creation Law which regulates severance pay and wages removes several important points that are detrimental to the community because they are considered as deprivation of the rights of workers/laborers, which rights have been regulated in Article 28 D paragraph (3) of the 1945 Constitution. The research method uses normative research with a statutory approach. The data used are various journals related to the topic the author is studying, related laws and regulations and several news sources from print and electronic media. The new regulations contained in the content material of the Job Creation Law should provide even better rules because the system used is the Omnibus Law which in its application accommodates many laws which are reduced to one rule so that there is simplification and avoids overlapping rules. However, in reality the Job Creation Law failed to accommodate many regulations, especially regarding wages and severance pay, thus triggering a lot of opposition/rejection from the community, especially workers/laborers.